2003
DOI: 10.1017/s0376892903000407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social, management and enforcement factors on the long-term ecological effects of marine sanctuaries

Abstract: Marine sanctuaries are increasingly being promoted as tools for conservation and fisheries management. This study investigates the effects of protection over 19 years on substrate composition and fish communities in four marine sanctuaries and corresponding non-sanctuary areas in the Philippines and examines the importance of community support, management measures and enforcement of regulations on these ecological effects. Between 1981 and 2000, substrate cover variables were measured using line transects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 33 publications
6
63
0
2
Order By: Relevance
“…10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54]. Moreover, Latin America saw more studies of state regimes reportedly performing similarly to open access regimes than Asia and Africa combined.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…10), except for 2 studies with undetermined outcomes [47,48]. There were more reported studies of state regime performing similarly to open access [49][50][51][52][53] than community performing similarly to open access [54]. Moreover, Latin America saw more studies of state regimes reportedly performing similarly to open access regimes than Asia and Africa combined.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
“…In two studies [50], similar performance with open access was reported in the absence of monitoring and high resource use pressure. Overall, regime characteristics were not broadly discussed, and we noted only three studies [51,55,56] that discussed positive regime characteristics.…”
Section: Results From Fisheries Resource Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlined fish groups had significant density between categories. Refer statistics given in Table 3 Coral Reefs (2009) 28:809-822 817 sites suggests that the Philippine reserves have more complex, resource-rich reef habitats compared with the fished reefs (see Christie et al 2002;Walmsley and White 2003). If the current inter-reef disparity of habitat conditions reflects those at the time of designation of the reserve, then this may eventually translate into the disparate values for the metrics of performance (e.g., fish density) between reserves and fished reefs, in favor of the reserve.…”
Section: Discussionmentioning
confidence: 99%